Stargazers - Gibbons, Gail (Gibbons, Gail. Explore the world with Gail Gibbons., 2023)
"Vetted by an expert, this new and updated edition introduces scientific facts about the stars, as well as how we look at and learn about them, through simple text and bold illustrations. From ancient names for constellations to modern innovations in telescope technology, this book covers a broad range of ideas without overwhelming the reader. It introduces and reinforces important vocabulary for the aspiring astronomer, explaining everything in clear, simple phrases. This book includes a brief timeline of major advances in astronomy, written in concise, kid-friendly language, and a wealth of fun facts and trivia about the stars"--